2003
DOI: 10.1213/01.ane.0000066017.66951.7f
|View full text |Cite
|
Sign up to set email alerts
|

Survival with Full Neurologic Recovery After Prolonged Cardiopulmonary Resuscitation with a Combination of Vasopressin and Epinephrine in Pigs

Abstract: We present a study to evaluate the effects of a combination of vasopressin and epinephrine during prolonged cardiopulmonary resuscitation on neurological outcome in pigs. We found that all pigs treated with a combination of vasopressin and epinephrine could be resuscitated and had full neurologic recovery observed over an entire period of 5 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 14 publications
0
18
0
4
Order By: Relevance
“…As this study was not designed to evaluate longterm survival and neurologic function, we are unable to assess whether a high cerebral blood flow in the AVP and the AVP/EPI/NE group might have beneficial effects on neurologic outcome after restoration of spontaneous circulation. However, in a previous porcine model of CPR, repeated administration of EPI together with AVP ensured long-term survival with full neurologic recovery (32).…”
Section: Discussionmentioning
confidence: 92%
“…As this study was not designed to evaluate longterm survival and neurologic function, we are unable to assess whether a high cerebral blood flow in the AVP and the AVP/EPI/NE group might have beneficial effects on neurologic outcome after restoration of spontaneous circulation. However, in a previous porcine model of CPR, repeated administration of EPI together with AVP ensured long-term survival with full neurologic recovery (32).…”
Section: Discussionmentioning
confidence: 92%
“…They found that coronary perfusion pressure, left ventricular myocardial blood flow, and ROSC rates were higher in the 45 and 90 mcg/kg groups compared to the two lower dose groups. Further studies established that the combination of epinephrine and vasopressin was superior in the swine model of ventricular fibrillation, 41, 42 pulseless electrical activity, 43 asphyxial cardiac arrest 4446 and recently in the swine model of bupivacaine-induced cardiac arrest. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Mayr et al[26] confirmed that the combined application of vasopressin and epinephrine rapidly elevated coronary perfusion pressure and the return of spontaneous circulation in pigs during cardiopulmonary resuscitation. Stadlbauer et al[27] observed that the combined application of vasopressin and epinephrine obviously increased coronary perfusion pressure, and returned spontaneous circulationin patients. Another study suggested that cerebral blood flow was reduced in patients treated with both vasopressin and epinephrine compared with those treated with vasopressin or epinephrinealone[28].…”
Section: Discussionmentioning
confidence: 99%